Taxation of Dividend Income and Economic Growth: The Case of Europe - Margareta Dackehag; Åsa Hansson (Lund University, School of Economics and Management, Department of Economics, 2015)
More recently researchers have turned to analyze how the tax structure, rather than the overall tax level, affects economic performance. For instance, several papers have investigated how taxation on corporate and individual (labor) income influences growth. Taxation of dividend income may also influence growth via its impact on investments and firm behavior. Within the academic community there is conflicting views about the impact taxation of dividends has on firm behavior and, hence, on economic performance. According to the "traditional view", taxation of dividends is distortionary and increases the cost of equity. According to the "new view", taxation of dividends does not influence the marginal cost of capital and consequently has no impact on investment decisions. To our knowledge, this paper is the first study to explore how tax rates on dividends affect economic growth, by using panel data from 1990 till 2008 for 18 European countries. We find that taxation of dividend income negatively influences economic growth, a result that corroborates the old view of dividends taxation as distortionary and also has some policy implication for the European countries in question.
Keywords: H21; H24; H25; O40; 330; Economic growth; taxation of corporate income; taxation of personal income